Toxicity and oxidative stress induced by semiconducting polymer dots in RAW264.7 mouse macrophages. Issue 22 (14th June 2015) - Ye, Fangmao; White, Collin C.; Jin, Yuhui; Hu, Xiaoge; Hayden, Sarah; Zhang, Xuanjun; Gao, Xiaohu; Kavanagh, Terrance J.; Chiu, Daniel T.
<x xml:space="preserve">Abstract</x> This paper describes a systematic study of PDot on RAW264.7 cells.